Influence Financial Distress, Firm Size, and Leverage on Audit Delay with Auditor Reputation as Moderating Variable - Hasmaynelis Fitri; Dessy Haryani; Ramdani Bayu Putra; Sri Annisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
This study aims to examine how much influence Financial Distress, company size, and Leverage have on Audit Delay with Auditor Reputation as a Moderating Variable in All Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 Period. Sampling in the study using the method of purposive sampling obtained 32 companies with a research period of 5 years. The analytical method used in this study is panel data regression analysis with Fixed Effect estimation results using Eviews 9. The results showed that financial distress partially had a positive effect, company size partially had a positive and significant effect on audit delay, while leverage had a positive effect on audit delay.